PEMBERDAYAAN HUKUM BUMDES DAN UMKM DESA PANCASAN, KECAMATAN AJIBARANG, KABUPATEN BANYUMAS - Prianto, Yuwono; Suni, Indri Elena; Aurelia, Jessica; Aprianes, Cesilia (Jurnal Serina Abdimas, 2024)
Villages have evolved in a variety of ways, and they must be safeguarded and empowered to become strong, advanced, independent, and democratic in order to lay a solid foundation for governance and growth toward a just, prosperous, and wealthy society. BUM Desa or Village-Owned Enterprise is a legal entity established by the Village that is useful for managing businesses, utilizing assets, developing investment and productivity, providing services, and/or providing other types of businesses aimed at the welfare of the Village community to the greatest extent possible. Through this abdimas activity, there are several problems that want to be solved including the limited knowledge and understanding of the legal aspects of entrepreneurship of Bumdes administrators and MSME players and the lack of education of Pancasan Village MSME players so that the team provides entrepreneurial knowledge to Pancasan villagers in starting and building their business. There are several tests and practices that can add to the experience of the participants as well as games to strengthen team building. Furthermore, based on the activities that have been carried out, conclusions are formulated and suggestions are sought to help develop existing shortcomings. ABSTRAK Desa harus dilindungi dan diberdayakan untuk menjadi kuat, maju, mandiri, dan demokratis. Ini akan membangun landasan yang kuat untuk pemerintahan dan kemajuan menuju masyarakat yang adil, makmur, dan sejahtera. BUM Desa atau Badan Usaha Milik Desa suatu badan hukum yang didirikan oleh Desa yang bermanfaat untuk mengelola usaha, memanfaatkan aset, mengembangkan investasi dan produktivitas, menyediakan jasa pelayanan, dan/atau menyediakan jenis usaha lainnya yang bertujuan untuk kesejahteraan masyarakat Desa sebesar-besarnya. Melalui kegiatan abdimas ini, ada beberapa masalah yang ingin diselesaikan diantaranya keterbatasan pengetahuan dan pemahaman aspek hukum mengenai kewirausahaan pengurus Bumdes dan pelaku UMKM serta Minimnya tingkat pendidikan pelaku UMKM Desa Pancasan sehingga tim memberikan pengetahuan berwirausaha kepada warga desa Pancasan dalam memulai serta membangun bisnisnya. Adapun beberapa tes-tes dan praktik-praktik yang mampu menambah pengalaman para peserta juga permainan-permainan sebagai penguatan team building. Selanjutnya, berdasarkan kegiatan yang telah dilaksanakan lalu dirumuskan kesimpulannya serta mencari saran dalam membantu mengembangkan kekurangan yang ada.